Heterologous expression of a barley boron transporter gene in tobacco (Nicotiana tabaccum) and analysis of transgenic plants - Gumusel, Doga; Oz, M. Tufan; Eyidogan, Fusun; Yucel, Meral; Ciftci, Yelda Ozden; Oktem, Huseyin Avni (Elsevier Science Bv, 2012)
[No abstract available]